The Contribution of Protein Intake and Training Frequency to Cardiovascular Endurance of Kendari Rowing Athletes - A Asmuddin; Muhtar Asshagab; S Sariul; J Jud (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
The aim of the study was to analyze the contribution of protein intake and exercise frequency to the cardiovascular endurance of rowing athletes in the Student Sports Education and Training Center, known as PPLP, in Kendari. The research sample consisted of 50 athletes, including 25 junior PPLP rowing athletes aged 16-19 years and 25 formers senior PPLP rowing athletes aged 25-30 years. This research included an observational study with a cross-sectional design. The collected data were analyzed using the Pearson and Spearman correlation statistics tests. The instrument for measuring protein intake was the Nutrition Adequacy Rate based on WNPG VII 2019. Exercise frequency data were obtained through interviews using a questionnaire. Cardiovascular endurance was measured by the athlete’s maximum mileage from a 15-minute running test. The results of the Spearman correlation test between exercise frequency and cardiovascular endurance showed no significant results (p 0.05). Exercise frequency had a significant positive relationship with cardiovascular endurance (p = 0.004, r = 0.395). It showed that there was a significant relationship between protein intake and cardiovascular endurance (p = 0.003, r = 0.415). The junior rowing athlete group generally had moderate cardiovascular endurance (80.0%), while the former senior rowing athlete group generally had sufficient (48.0%) and less (44.0%) cardiovascular endurance. On average, the cardiovascular endurance of the junior rowing athlete group (40.1 ml O2/kg BW/min) was higher and significantly different (p 0.05) compared to the former senior rowing athlete group (36.2 ml O2/kg BW/min). Athletes with normal protein intake (75%) had a good cardiovascular endurance. Most athletes with normal protein intake had sufficient cardiovascular endurance (45.4%). Meanwhile, the athlete with a severe protein deficiency had less cardiovascular endurance (38.4%). This study concludes that the higher the sports activity, the higher the need for protein consumption, which eventually increases the work function of the heart, especially in rowing athletes in PPLP Kendari.